Foundations of American Education A Critical Lens - Wells , Melissa; Clayton, Courtney (Open textbook library., 2021)
In this survey text, readers will explore the foundations of American education through a critical lens. Topics include the teaching profession, influences on student learning, philosophical and historical foundations, structures of schools, ethical and legal issues, curriculum, classroom environment, and the path forward.